Funkcja szkoły w zapobieganiu wad postawy ciała u dzieci = Role of school in the prevention of body posture defects in children - Skorupka, Ewa; Asienkiewicz, Ryszard (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The study was conducted in the years 2006-2010 and it included children from 12 primary schools from Lubuskie and Lower Silesia Provinces. A total of 2071 children aged 7-10 and their parents were examined, and the school directors, teachers running corrective and compensatory gymnastics classes and school nurses were interviewed. It was found that every fourth child in the schools under research participated in corrective gymnastics classes, and the boys attended them slightly more often than the girls did.
Keywords: body posture disorders; early school age; comparative characteristics; prevention; wady postawy; wiek wczesnoszkolny; charakterystyka porównawcza; profilaktyka